Phlebotomine sand flies (Diptera: Psychodidae: Phlebotominae) in urban rainforest fragments, Manaus - Amazonas State, Brazil - Rocha, Liliane Coelho da; Freitas, Rui Alves de; Franco, A. M. (Acta Tropica, 2013)
The non-flooded upland rainforest fragment in the Federal University of Amazonas Campus is considered one of the world's largest urban tropical woodland areas and Brazil's second largest one in an urban setting. It is located in the city of Manaus, State of Amazonas at 03° 04' 34' S, 59° 57' 30' W, in an area covering nearly 800 hectares. Forty-one (41) sand fly species belonging to genus Lutzomyia were found attaining a total of 4662 specimens collected. Lutzomyia umbratilis was the dominant species at all heights, followed by Lutzomyia anduzei and Lutzomyia claustrei. The fauna alpha diversity index showed to be 6.4, which is not much lower than that reported for areas of continuous forest in this Amazonian region. This data provides additional evidence on Phlebotomine sand flies found to transmit Leishmania and other trypanosomatids to humans and other animals circulating in this area. This is the first study being reported on sand flies collected in an urban rainforest fragment in Amazonia. © 2013 Elsevier B.V.
Keywords: Diversity Index; Fly; Habitat Fragmentation; Rainforest; Upland Region; Urban Area; Woodland; Fauna; Geography; Kinetoplastida; Leishmania; Lutzomyia; Lutzomyia Anduzei; Lutzomyia Claustrei; Lutzomyia Umbratilis; Nonhuman; Parasite Transmission; Psychodidae; Rainforest; Tropics; Urban Area; Animal; Cities; Female; Humans; Insect Vectors; Leishmania; Leishmaniasis; Male; Psychodidae; Rain; Trees; Tropical Climate; Urban Health; Amazonas; Manaus; Animalsia; Diptera; Lutzomyia Umbratilis; Phlebotominae; Psychodidae; Trypanosomatidae